An approach to GIS-based traffic information system using Spatial Oracle. (6th November 2019) - Barman, Subhas; Sarkar, Atanu; Roy, Rajat Kamal; Saha, Sourav; Rajak, Kajal; Sarkar, Joydeep
Traffic congestion is a threat to the economical, environmental, social and sustainable development of a city. The traffic management has always been an issue of concern for urban areas of a city. Geographic information system (GIS) offers an effective solution to the traffic management of a city and it helps the peoples to find out necessary information regarding traffic, road, location and direction of a destination. General traffic system is limited in data sharing and it is difficult to achieve integration in data processing. In this work, an urban traffic management system based on geographic information system (GIS) is implemented to handle the roads, landmarks, sensitive areas and traffic information for urban traffic police locus. Our work solves various traffic related problems and retrieves the traffic centres that have to be alert in different situations. The detected shortest path is visualized with the connected paths in our approach.